Tachykinin Expression Levels Correlate with Caste-Specific Aggression in Workers of the Leaf-Cutting Ant Acromyrmex echinatior - Howe, Jack; Schiøtt, Morten; Boomsma, Jacobus J. (Frontiers in Ecology and Evolution, 2016)
The tachykinins are a family of neuropeptides that influence a range of behavioral phenotypes in both vertebrates and invertebrates; they appear to have a conserved role in the processing of stimuli, and in the control of aggression in a wide range of animals. Expression of tachykinin in a cluster of neurons was recently shown to determine the stimulus response threshold for aggressive behavior in Drosophila (1). Varying response thresholds are often implicated in division of labor within social insect colonies, so we hypothesized that Tachykinin could play a role in the organization of colony defense by affecting individual response thresholds to non-nestmate stimuli. We used quantitative-PCR in combination with behavioral assays to test for associations between the expression of Tachykinin and its receptor, and the aggressive division of labor among the castes of the leaf-cutting ant Acromyrmex echinatior, a species with multiple worker castes. After correction for differences in brain size among castes, we found that the most aggressive large worker caste had the highest Tachykinin expression levels, but that no such effect was apparent for breeding and virgin queens. To further evaluate these deviating results for the reproductive caste, we manipulated the aggression threshold of virgin-queens by removing their wings, which is known to make them express a soldier-like behavioral phenotype. Despite heightened aggression, expression levels of Tachykinin remained unaffected, suggesting that aggression levels in reproductive caste phenotypes are controlled by differential expression of other genes.